PENGARUH PENGGUNAAN APLIKASI ANDROID CERITA ANAK BERBASIS PENGUATAN PENDIDIKAN KARAKTER TERHADAP HASIL BELAJAR SISWA KELAS 4 SD - Arinta Rezty Wijayaningputri; Innany Mukhlishina; Murtyas Galuh Danawati (Jurnal Holistika, 2022)
The current development of technology-based education is growing rapidly, so that the world of compulsory education can use technology. Especially in the 21st century, smartphone media is a tool for online-based learning. That's why there are many benefits of smartphone media that students can use to learn online. SD Muhammadiyah 8 Dau has used media with various learning methods for face-to-face learning, but online learning media is still very limited. In addition, teachers have difficulty whether the media used has an effect or not on student learning outcomes, especially fourth grade students. The results of the interviews also showed that in class IV there was no media for learning children's stories that were in accordance with the applicable curriculum. Especially for children's story-based learning media to strengthen character education. In fact, the government is currently promoting the cultivation of character education for students in elementary schools. Related to the problems above, the purpose of this study is to measure the effect of utilizing the use of android applications as learning tools based on strengthening character education on student learning outcomes. This research was conducted at SD Muhammadiyah 8 Dau, Malang Regency. The design of this research is pretest-posttest-group design, with a simple random sampling method that is determined based on the results of the pretest posttest. The results obtained through the analysis showed the results of the average pretest value of 79.38 and the posttest average value of 84.38. In addition, the results of the T-Test in the Sig. (2-Tailed) table have a value of 0.150 where the value > 0.05 means that H1 is accepted. So it can be stated that there is an effect of using the android application for children's stories on the learning outcomes of fourth grade students at SD Muhammadiyah 8 Dau.